FORMS OF COMMUNITY PARTICIPATION IN THE DEVELOPMENT OF THE TOURIST VILLAGE OF GENGGELANG, NORTH LOMBOK DISTRICT - Intan, Intan Maharani Asmara; Sri Susanty (Faculty of Economics and Business, University of Mataram, 2022)
The problems studied in this research are related to the development of the Genggelang Tourism Village, North Lombok Regency regarding the forms of participation carried out by the community. The research method used is descriptive with a qualitative approach conducted in Genggelang Tourism Village, North Lombok Regency. Data collection techniques were observation, interviews, and documentation with informants including the Penjor Hamlet Pokdarwis, Kertaraharja Hamlet Pokdarwis, and Gangga Hamlet Pokdarwis. Data analysis uses Miles and Hubermen (1992) where data analysis is carried out interactively and takes place continuously until the data obtained becomes complete. The results of this study indicate that the form of community participation is divided into 4 forms of participation, namely the participation of money, property, labor, and skills. This form of community participation is carried out based on supporting and inhibiting factors in the Genggelang Tourism Village. supporting and inhibiting factors are divided into 3 hamlets. Where each of these hamlets has a tourist destination. So the form of community participation in Genggelang Tourism Village is also divided into each of the related hamlets. The information contained in this paper is expected to be able to assist in increasing community participation in the Genggelang Tourism Village, North Lombok Regency.